What the ancients did for us the islamic world - Cameron, Jane; Aslett, Will; BBC Educational and Training; Open University ([S.l.] : BBC Active, 2006)
In this video, Adam Hart-Davies uncovers the most influential developments of each of the great civilization of the past, leading viewers through the history of inventions, while rebuilding and testing some of his favourite in the studio
ep.1. The Islamic world
Title from disc label
Executive producer, Martin Mortimore, John Farren ; film editor, Chris Roberts ; graphics, Chris Rolf
Presenter: Adam Hart-Davies
Keywords: Civilization, Ancient; Civilization, Islamic